2014
DOI: 10.1159/000365673
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Significance of Serum and Tissue Galectin 3 Expression in Patients with Carcinoma of the Bladder

Abstract: Background: Galectins are group of proteins found in the cytoplasm, nucleus, cell surface and extracellular matrix. Galectin 3 (Gal-3) displays pathological expression in a variety of processes such as tumorigenesis. Patients and Method: 70 patients classified into the control group, cystitis group, transitional cell carcinoma group, and squamous cell carcinoma group were enrolled in this study which aimed to detect the serum level and the intensity of tissue expression of Gal-3. Results: Both serum level and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Serum galectin-3 levels were increased in patients with transitional cell carcinoma compared with squamous cell carcinoma. Patients with high-grade transitional cell carcinoma had a significantly increased serum galectin level compared with those with low-grade tumors, as did those with muscle-invasive transitional cell carcinoma compared with papillary non-invasive tumors ( 158 , 159 ). These results indicated that galectin-3 may be a potential diagnostic biomarker for bladder cancer.…”
Section: Galectin-3 and Cancermentioning
confidence: 92%
“…Serum galectin-3 levels were increased in patients with transitional cell carcinoma compared with squamous cell carcinoma. Patients with high-grade transitional cell carcinoma had a significantly increased serum galectin level compared with those with low-grade tumors, as did those with muscle-invasive transitional cell carcinoma compared with papillary non-invasive tumors ( 158 , 159 ). These results indicated that galectin-3 may be a potential diagnostic biomarker for bladder cancer.…”
Section: Galectin-3 and Cancermentioning
confidence: 92%
“…The recurrence rate after cystectomy approaches 50%, indicating that this treatment alone might not be optimal for some patients [4] . Targeted therapy is a novel treatment strategy in oncology, targeting specific signalling pathways within the malignant cells, and that might enhance the cytotoxic effect but with fewer adverse events [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Gal-3 could inhibit cell apoptosis, it could also facilitated angiogenesis by its carbohydrate recognitiondomains (CRDs) (24) .These finding is consisting with the earlierstudiesshowed that elevated Gal-3 is dangerous, the depth of invasion, lymph nodemetastasis, distant metastasis and TNM stages in different kind of cancer was associated with Gal-3 level (25,26,27) . However, Gendya H,et al (28) failed to demonstrate this relation and informed no major sta tistical change in serum Gal-3 levels indiverse stage and grade of bladder cancer.…”
Section: Discussionmentioning
confidence: 96%